2011
DOI: 10.1136/bmjopen-2011-000118
|View full text |Cite
|
Sign up to set email alerts
|

Screening for congenital cytomegalovirus infection using newborn urine samples collected on filter paper: feasibility and outcomes from a multicentre study

Abstract: BackgroundAs congenital cytomegalovirus (CMV) infection causes significant clinical consequences not only at birth but also later as neurological sequelae, it is critical to establish a strategy for screening congenitally infected newborns. Previous studies have identified an insufficient sensitivity in screening methods based on the use of dried blood spots (DBSs).ObjectivesTo evaluate the feasibility of the authors' recently developed method for large-scale screening for congenital CMV infection and to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
100
4
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(109 citation statements)
references
References 38 publications
3
100
4
2
Order By: Relevance
“…These patients might otherwise not have been diagnosed with congenital CMV infection, because typical clinical manifestations such as microcephaly and hepatosplenomegaly were absent. In the recent universal CMV screening conducted in Japan, CMV was identified in 0.3% of newborns, and SNHL was observed in 12% of infected cases [15]. If these frequencies are applied to our study population, the predicted number of congenital CMV-related SNHL is 7.5, which is close to the number of cases identified in this study.…”
Section: Discussionsupporting
confidence: 61%
“…These patients might otherwise not have been diagnosed with congenital CMV infection, because typical clinical manifestations such as microcephaly and hepatosplenomegaly were absent. In the recent universal CMV screening conducted in Japan, CMV was identified in 0.3% of newborns, and SNHL was observed in 12% of infected cases [15]. If these frequencies are applied to our study population, the predicted number of congenital CMV-related SNHL is 7.5, which is close to the number of cases identified in this study.…”
Section: Discussionsupporting
confidence: 61%
“…CMV is the most common congenital viral infection, with a birth prevalence of about 0.2z-2.2z in developed countries and 0.31z in Japan (1,2,15). Congenital CMV infection causes significant clinical consequences not only at birth but also later, presenting as neurological sequelae, including sensorineural hearing loss and developmental delay.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, Boppana et al [7] showed that CMV screening using saliva swabs had excellent sensitivity of 97.4-100% and specificity of 99.9%. Other investigators have utilized urine and umbilical cords for congenital CMV screening with some success [8,9], but the ease of collection of saliva swabs makes this method the currently preferred one for routine newborn screening [10]. A positive CMV saliva screen should be confirmed with a urine CMV PCR test or culture, as collection of saliva after breastfeeding could detect contamination from CMV present in breast milk rather than actual infection [11].…”
mentioning
confidence: 99%